Production and Characterization of Pectinase Through Solid-State Fermentation of Orange Peels by a Mutant Yeast Strain - Uroosa Ejaz; Asma Hanif; Ahsan Ali Khan; Laiba Jawad; Isha Rasheed; Bushra Noor; Amal S. Alswat; Muhammad Sohail (International Journal of Food Science)
Pectinases hydrolyze pectin in plant biomass and are commonly used in the fruit juice industry. In this study, pectinase produced by a mutant yeast strain, Geotrichum candidum AHC1, was characterized and used to clarify the orange juice. The strain AHC1 produced 76.08 IU mL−1 pectinase after fermenting orange peel powder under solid-state conditions. This yield was several folds higher than G. candidum AA15 (wild type) and Saccharomyces cerevisiae MK-157. Moreover, S. cerevisiae MK-157, G. candidum AA15, and G. candidum AHC1 produced 42.62, 58.28, and 75.28 IU mL−1 pectinase, respectively, under submerged fermentation. Consequently, pectinase from AHC1 was characterized by using a central composite design. Results indicated that pectinase from AHC1 exhibited maximum activity at 35°C, 16.47 min reaction time, 1.89% substrate concentration, and pH 5.4. Under optimized conditions, the preparation exhibited 87 IU mL−1 pectinase activity, which was correlated with the predicted value (95.13 IU mL−1). Furthermore, Km of the crude pectinase (16 mg mL−1) was found to be greater in comparison to the purified pectinase, demonstrating its high affinity to pectin. The treatment of orange juice with pectinase resulted in increased yield and clarity within 30 min. This study provides prospects for a citrus circular bioeconomy by utilizing orange peels to produce pectinase and subsequently using pectinase to clarify orange juice.